Acardius Acephalus Amorphous Foetal Monster Co-twined with a Normal Live Calf in a Crossbred Cow at Field Level - Chidambaram, Pugazharasi; Narayanasamy, Arunmozhi; Velmurugan, Jaganath; Thulasiraman, Sarath (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Acardius acephalus is a rare congenital malformation characterized by the absence of a functional heart andhead. This is a form of detached asymmetric conjoined twinning in which one of the twins (the parasite) is joinedto a relatively normal fetus (the autosite) in one of the same sites of union as intact conjoined twins (Spencer, 2001).